Intergenerational transmission of attachment: A qualitative study on eight adopted children - Hillman, Saul; Lajmi, Nahed; Nezi, Katerina; Steele, Miriam; Hodges, Jill; Simmonds, John; Kaniuk, Jeanne (Adoption & fostering, 2025)
This study reports on the attachment representations of eight late-adopted adolescent individuals, as well as the similarities and differences in their narratives based on whether they were placed with adoptive parents, who were characterised as securely or insecurely attached according to the Adult Attachment Interview (AAI). A thematic analysis drew upon data from two different measures (Story Stem Assessment Profile and Friends and Family Interview) at early childhood and early adolescence, and subsequently classified findings into two categories: positive representations/attachments and negative representations/attachments. Within the first category, the young individuals demonstrated themes of seeking, offering and receiving help, as well as viewing significant others as emotionally supportive. Within the second category, themes illustrated adults as vulnerable, neglectful and hostile, and young individuals as violent and with a relatively negative view of the self. For young people adopted by ‘secure’ parents, positive representations showed a progressive increase from childhood to adolescence and negative representations a marked decrease in adolescence. Such findings contribute to attachment research, exploring the intergenerational transmission of attachment beyond childhood, as well as in adoptive families where the identified attachment model of both parents is assessed. They also have important implications for adoption services and the support made available for adoptive families. Plain language summary This study reports on the attachment representations of eight late-adopted adolescent individuals: four placed with securely attached and four with insecurely attached adoptive parents. This study analysed these eight children’s narratives in childhood (using a narrative task) shortly after placement and attachment interviews carried out in early adolescence. Themes from these narratives and interviews indicated both positive representations/attachments and negative representations/attachments. Over time, young people adopted by ‘secure’ parents showed a greater increase in positive representations and decrease in negative ones. These findings add to our knowledge of attachment research, particularly within the field of adoption, exploring the possible intergenerational transmission of attachment from parents to children. This study has important implications for policy and practice, with the scope for adoption services to provide more tailored support for adoptive families.